Tailoring Human Milk Oligosaccharides to Prevent Necrotising Enterocolitis Among Preterm Infants - Abbas, Safiyyah; Keir, Amy K.; Makrides, Maria; Klein, Laura D.; Grzeskowiak, Luke E.; McPhee, Andrew J.; Rumbold, Alice R. (Frontiers in Nutrition, 2021)
Necrotising enterocolitis (NEC) is a devastating disease affecting preterm infants, with little improvement in mortality rates and treatment strategies in the last thirty years. Human milk oligosaccharides (HMOs) are emerging as a potential preventive therapy, with multiple protective functions postulated. Our aim is to summarise the evidence concerning the role of HMOs in NEC development and emerging strategies to tailor the delivery of HMOS to preterm infants. Most research efforts to date have focused on supplementing preterm infants with simple oligosaccharides, which are structurally different to HMOs and derived mainly from plants. Clinical trials demonstrate limited benefits for NEC prevention arising from the use of these supplements. Alternative strategies under investigation include optimising HMOs for infants receiving donor human milk, concentrating oligosaccharides from donor human milk and from animal milks, as well as more sophisticated synthetic oligosaccharide production strategies. Critically, high quality evidence to support implementation of any of these approaches in the neonatal unit is lacking. Whether it is a specific HMO alone or a combination of HMOs that exert protective effects remains to be elucidated. Further challenges include how best to manufacture and administer oligosaccharides whilst retaining bioactivity and safety, including evaluation of the long-term effects of altering the balance of HMOs and gut microbiota in preterm infants. While several human clinical trials are underway, further research is needed to understand whether a tailored approach to oligosaccharide supplementation is beneficial for preterm infants.